“La saccharina como suplemento alimenticio en el engorde de cobayos (Cavia porcellus) en el cantón Centinela del Cóndor, provincia de Zamora Chinchipe” - Cuenca Maza, Luis Ángel (2023)
In the rural sector of Zamora Chinchipe, particularly in the Centinela del Cóndor Canton, Zumbi parish, breeders engaged in guinea pig farming have been facing different sort of challenges related to the low profitability of their breeding and management activities lately. This is primarily attributed to various unfavourable factors, including the poor quality of forage. Consequently, there is a need to explore alternative feeding options. Hence, the current research project titled "The Use of Sugar Cane Saccharina (Saccharum officinarum) as a Nutritional Supplement in Guinea Pig (Cavia porcellus) Fattening in the Centinela Canton of Cóndor, Zamora Chinchipe Province" aimed to achieve the following objectives: determine the accurate productive parameters of guinea pigs during the fattening stage using sugar cane saccharina, assess the profitability in guinea pig meat production with the inclusion of sugar cane saccharina, and disseminate the research findings among guinea pig producers in the study area. To achieve these mentioned objectives, a randomized block experimental design was employed, consisting of three treatments with three repetitions each, totalling 36 experimental units. The analysed variables included feed consumption, weight gain, feed conversion, mortality, carcass yield, and profitability. The results revealed that treatment 1, comprising 60% grass and 40% saccharina in the guinea pig diet, exhibited superior feed consumption at 306.1 g. Additionally, it reported a higher average weight gain of 13.12 g per day. In terms of profitability, treatment 1 demonstrated greater profit at 1.88 dollars per animal compared to 1.28 dollars for treatment 3. Consequently, the study concluded that saccharina is a viable alternative for guinea pig feeding. Moreover, financial indicators have confirmed the profitability of the activity when incorporating this food supplement into the daily-basis guinea pig diet.